2017
DOI: 10.3390/ani7030018
|View full text |Cite
|
Sign up to set email alerts
|

Factors Which Influence Owners When Deciding to Use Chemotherapy in Terminally Ill Pets

Abstract: Simple SummaryCancer is as common amongst pets as it in humans. Chemotherapy can be integrated into treatment regimes for terminally ill pets to attempt to shrink tumours to extend life expectancy, but it does not cure cancer and it can have negative side effects including vomiting, depression and behavioral changes. To date, little research has been undertaken to explore owners’ decisions whether or not to treat their animals with chemotherapy. Seventy-eight dog and cat owners completed an online questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…For example, factors identified from previous research include the animal’s quality of life (QoL), the owner’s finances, time and other resources, and their attachment to their cat [ 32 , 33 , 34 , 35 ]. Many of the factors in other previous studies were identified via ‘expert’ consensus [ 36 ], or used in surveys [ 29 , 37 ], and therefore the information collected may not reflect owner perceptions but expert consensus, or has been limited to quantitative data via surveys or structured interviews. For example, Slater at al.…”
Section: Introductionmentioning
confidence: 99%
“…For example, factors identified from previous research include the animal’s quality of life (QoL), the owner’s finances, time and other resources, and their attachment to their cat [ 32 , 33 , 34 , 35 ]. Many of the factors in other previous studies were identified via ‘expert’ consensus [ 36 ], or used in surveys [ 29 , 37 ], and therefore the information collected may not reflect owner perceptions but expert consensus, or has been limited to quantitative data via surveys or structured interviews. For example, Slater at al.…”
Section: Introductionmentioning
confidence: 99%
“…Concerns that the animal is being kept alive for the owner are not unique to chemotherapy and consideration should be a given to whether veterinarians should initiate a treatment just because they can [5]. However, in balancing the interests of the owner, animal and veterinarian there is the added dimension that chemotherapy involves the use of drugs that are mutagenic, carcinogenic, teratogenic and may be irritant [32], and there has been limited research on treatment decision-making by owners with animals diagnosed with malignancies [31].…”
Section: Discussionmentioning
confidence: 99%
“…There are other significant concerns with the use of chemotherapy in dogs. Owners of animals undergoing chemotherapy may be poorly informed and despite the fact that chemotherapy is becoming a more common therapy there have been no large scale studies on the prevalence and incidence of side-effects associated with this treatment [32]. Of additional concern is that the public health risks associated with the use of chemotherapeutic agents may not be given adequate attention in veterinary practice [43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations